BLACK MALES TEACHING TODDLERS?! AN EXAMINATION OF HOW BLACK MALE YOUTH PARTICIPATING IN A GROW YOUR OWN (GYO) TEACHER PIPELINE PROGRAM MADE DECISIONS CONCERNING A LONG-TERM CAREER IN EARLY CHILDHOOD EDUCATION - (:unkn) unknown (My University, 2024)
Despite research (Cormier et al., 2022; Lindsay & Hart, 2017) highlighting the positive impact Black male educators have on Black students, and Black male students in particular, the representation of Black, non-Hispanic male teachers in the U.S. public and private K-12 teaching workforce remains notably low at 1.3% (Taie & Lewis, 2022). This scarcity is evident across the entire PK-12 education continuum, which includes early childhood education (ECE). This qualitative study examined the experiences of eight Black male youth who participated in The Young Black Male Teacher Project (TYBMTP), a grow-your-own (GYO) teaching exposure pipeline program that affords young Men of Color, ages 18-24, the opportunity to explore teaching as a viable career option by working alongside a lead or licensed certified teacher providing early literacy intervention instruction to students in PreK-3 and PreK-4 classrooms for an academic school year. The study explored how participants, known as “Scholars,” during their tenure with TYBMTP, decided whether to pursue or not pursue early childhood education (ECE) as a viable career option post their participation in TYBMTP. The study employed semi-structured interviews, concept maps, a focus group, and two theoretical frameworks (critical race theory and hegemonic masculinity theory) to understand and ascertain to what degree, issues of race, racism, masculinity, or other factors influenced participants' decision-making. The investigation revealed five critical factors shaping Black males' decision to either pursue or not pursue ECE as a long-term career. For most participants (6 out of 8), the three critical factors that shaped their decision to pursue ECE as a career included pedagogical relations with students, career exposure, and teaching as a counter-narrative. In contrast, the remaining participants (2 out of 8), who opted not to pursue teaching careers in ECE, cited poor compensation and burdensome pathways to teaching as deterrents. The study adds to current scholarly discourse on recruiting and retaining Black male teachers in ECE by shedding light on the lived experiences of multiple Black males functioning as prospective educators in early childhood education, a context in which they are rarely seen functioning as guardians, nurturers, and caregivers of young children. The research also offers insight into some of the most critical factors influencing Black males' decision-making processes specifically around whether to pursue or not pursue ECE as a viable long-term career option. Finally, the study provides recommendations on actions schools, school districts, policymakers, and education practitioners can employ to attract and recruit more Black males to embark on teaching careers in ECE.